Evaluasi Online Sales Kit Menggunakan IT Balanced Scorecard Pada PT Bank Sumsel Babel - Asoka, Egga; Rahmi, Lailatur; Afdhaluddin, Muhammad (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
This study aims to develop a measurement model with a variety of indicators that can be used to evaluate online sales kit at PT. Bank Pembangunan Daerah Sumatera Selatan Bangka Belitung, Tbk. As the basis to build the measurement model, concept of IT Balanced Scorecard are being used to find relevant indicators in 4 dimensions, namely Business Contribution, User Orientation, Operational Excellence and Future Orientation. From the results of the literature research and journals that have been done previously, 18 indicators are found to define the factors on each dimension of IT Balanced Scorecard. By confirmatory factor analysis, it has been found that only 14 indicator are proven to be valid and significant. With this analysis, the measurement model which has been constructed has proven to be a valid measurement model to evaluate system for the company